2017
DOI: 10.1088/1361-6560/aa6674
|View full text |Cite
|
Sign up to set email alerts
|

Supersonic transient magnetic resonance elastography for quantitative assessment of tissue elasticity

Abstract: Non-invasive, quantitative methods to assess the properties of biological tissues are needed for many therapeutic and tissue engineering applications. Magnetic resonance elastography (MRE) has historically relied on external vibration to generate periodic shear waves. In order to focally assess a biomaterial or to monitor the response to ablative therapy, the interrogation of a specific region of interest by a focused beam is desirable and transient MRE (t-MRE) techniques have previously been developed to acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 68 publications
1
19
0
Order By: Relevance
“…However, it is a one-dimensional imaging technology and needs special mechanical vibrating device to generate shear wave, and cannot be used for patients with ascites, obesity and stenosed rib space stenosis [38]. It cannot take two-dimensional images to avoid the nontarget structure in the liver [7,39]. SWE is a newer elastic imaging technology which is a newer variant of RTE [40].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is a one-dimensional imaging technology and needs special mechanical vibrating device to generate shear wave, and cannot be used for patients with ascites, obesity and stenosed rib space stenosis [38]. It cannot take two-dimensional images to avoid the nontarget structure in the liver [7,39]. SWE is a newer elastic imaging technology which is a newer variant of RTE [40].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, MR-ARFI has been used for applications in other soft tissue targets for evaluating the focus and refocusing [176, 177]. The MR-ARFI technique has also been utilized for mechanical property evaluation by measuring either induced displacements or shear wave velocities [178, 179].…”
Section: Phase Aberration Correctionmentioning
confidence: 99%
“…Souchon et al showed that measuring transient shear waves in ex vivo biological tissues was also feasible . Using a small bore 7T scanner and large amplitude MEGs (140 mT/m), Liu et al demonstrated that 2D shear wave speed maps can be computed from these MR measured transient shear waves . Potential challenges to implementing this method clinically include the long acquisition time (~30 min for a 2D map) and use of MEG amplitudes that are not currently available on clinical whole‐body MRI systems.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of ultrasound (US) and MR elastography (MRE) methods have been developed to measure the shear wave speed (cs) or shear modulus (μ) of tissues. In an ideal elastic non‐dissipative medium, the speed of a propagating shear wave is related to the shear modulus by:μ=ρcs2…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation